METHODS FOR ASSESSING THE CYBERSECURITY OF CRITICAL STATE INFRASTRUCTURE - Adilzhanova, С.; Rakhysh, А.; Abdulkarimova, Г.; Gusmanova, Ф. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
In the context of increasing digitization and integration of technologies, protecting critical infrastructure from cyber threats is becoming a priority. Cyberattacks on such facilities can cause significant damage to the economy, national security, and the well-being of citizens. This article reviews modern methods for assessing the cybersecurity of critical infrastructure, including traditional and innovative approaches based on risk analysis, threat modeling, the use of Bayesian networks, scenario analysis, and hybrid methods. A review of 46 scientific studies on this topic is conducted, and the main trends and limitations of existing approaches are identified. Special attention is paid to the issue of adapting assessment methods for various industries and integrating cybersecurity with traditional security approaches. The article is intended for cybersecurity specialists and researchers involved in the development of new methods for assessing cybersecurity.